Endothelin-induced increases in vascular smooth muscle Ca2+ do not depend on dihydropyridine-sensitive Ca2+ channels. - Mitsuhashi, T (1989)
Endothelin is a potent mammalian vasoconstrictive peptide with structural homology to cation channel-binding insect toxins. We tested the proposal that this peptide directly activates dihydropyridine-sensitive Ca2+ channels in cultured vascular smooth muscle (VSM) cells. First, we found that cell Ca2+ can be altered in VSM by activation of voltage-operated Ca2+ channels. KCl-induced depolarization and the dihydropyridine Ca2+ channel agonist (-) Bay K 8644 (10 microM) both raised cell Ca2+ more than twofold; the effect of KCl was blocked by the inhibitory enantiomer, (+) Bay K 8644 (40 microM). Similar responses were observed in Chinese hamster ovary (CHO) cells. Synthetic endothelin (4 x 10(-8) M) raised Ca2+ in VSM but not CHO cells from 100 +/- 17 to 561 +/- 34 nM within 12 s. Ca2+ subsequently fell to basal levels after 30 min. Half maximal Ca2+ response was at 4 x 10(-9) M endothelin. Unlike endothelin, thrombin raised Ca2+ in both VSM and CHO cells. The Ca2+ responses to endothelin and thrombin were not affected by nicardipine (1 microM), (+) Bay K 8644, or Ca2+-free solutions. Lastly, both hormones caused release of inositol phosphates in VSM cells. However, the response to thrombin was more than 10-fold larger and was more rapid than the response to endothelin; the thrombin response was sensitive to pertussis toxin, while the response to endothelin was not. Thus endothelin, like thrombin, raises cell Ca2+ in VSM by mobilization of intracellular stores and not by activation of dihydropyridine-sensitive Ca2+ channels. However, their receptors are distinct and they exhibit important differences in signal transduction.